2004
DOI: 10.1016/j.virol.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of virulent, attenuated, and revertant passages of a North American porcine reproductive and respiratory syndrome virus strain

Abstract: Pigs were exposed to three passages of the NADC-8 strain of porcine reproductive and respiratory syndrome virus (PRRSV) to investigate the relationship between genotypic and phenotypic properties. Differences were found in the virulence of the three passages called virulent, intermediate, and avirulent. Avirulent virus was derived by attenuation of virulent virus in cell culture and intermediate virus was derived by passage of avirulent virus in a pig. Nucleotide sequence differences between virulent and aviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 29 publications
2
26
2
Order By: Relevance
“…The mechanisms involved in heart resistance to CVB3-HL1 are not known, but attenuation of viruses after passages through cell culture is an often-observed phenomenon (10,11,25); for example, the attenuated Sabine 1 strain, the oral live polio vaccine, was derived by several passages through cell culture (45). One possible explanation for our findings is that heart resistance may have resulted from an accelerated clearance of the virus by specific immunological mechanisms directed against the CVB3-HL1 mutant; however, the additional inability of CVB3-HL1 to infect the heart efficiently, or a combination of the two mechanisms, may also be responsible for the heart resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in heart resistance to CVB3-HL1 are not known, but attenuation of viruses after passages through cell culture is an often-observed phenomenon (10,11,25); for example, the attenuated Sabine 1 strain, the oral live polio vaccine, was derived by several passages through cell culture (45). One possible explanation for our findings is that heart resistance may have resulted from an accelerated clearance of the virus by specific immunological mechanisms directed against the CVB3-HL1 mutant; however, the additional inability of CVB3-HL1 to infect the heart efficiently, or a combination of the two mechanisms, may also be responsible for the heart resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these mutations are not necessarily related to in vivo virulence but rather to adaptation of the viral strain to the culture host cell (32)(33)(34)(35)(36)(37)(38). We surmise that the amino acid mutations in the nonstructural and structural protein regions of JXA1-R may play key roles in the attenuation of HP-PRRSV in this study.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the previous studies suggested that the amino acid substitutions identified are located in functional regions of the PRRSV genome, which are hypothesized to affect the viral replication, signal transduction, protein transport, and antibody neutralization processes associated with PRRSV (32)(33)(34)(35)(36)(37)(38). Many of these mutations are not necessarily related to in vivo virulence but rather to adaptation of the viral strain to the culture host cell (32)(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of virulent, attenuated, and revertant passages of a North American PRRSV strain indicates that, aa mutations between virulent and attenuated strains in NSP3-8 regions mainly distribute in NSP3, NSP5, and NSP7 [21]. Coincidentally, aa substitutions in NSP3-8 regions of GDQJ also distributed in NSP3 (N 257 ?…”
Section: Discussionmentioning
confidence: 99%